2019
DOI: 10.2147/idr.s219755
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Shigella</em>: Antibiotic-Resistance Mechanisms And New Horizons For Treatment</p>

Abstract: Shigella spp. are a common cause of diarrheal disease and have remained an important pathogen responsible for increased rates of morbidity and mortality caused by dysentery each year around the globe. Antibiotic treatment of Shigella infections plays an essential role in reducing prevalence and death rates of the disease. However, treatment of these infections remains a challenge, due to the global rise in broad-spectrum resistance to many antibiotics. Drug resistance in Shigella spp. can result from many mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
111
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 199 publications
(281 reference statements)
6
111
0
2
Order By: Relevance
“…Disease symptoms include fever, abdominal cramping, and inflammatory diarrhea characterized by the presence of neutrophils and, in severe cases, blood ( Kotloff et al, 2018 ). There is no approved vaccine for Shigella and antibiotic resistance continues to rise ( Ranjbar and Farahani, 2019 ). Shigella pathogenesis is believed to be driven by bacterial invasion, replication, and spread within colonic intestinal epithelial cells (IECs).…”
Section: Introductionmentioning
confidence: 99%
“…Disease symptoms include fever, abdominal cramping, and inflammatory diarrhea characterized by the presence of neutrophils and, in severe cases, blood ( Kotloff et al, 2018 ). There is no approved vaccine for Shigella and antibiotic resistance continues to rise ( Ranjbar and Farahani, 2019 ). Shigella pathogenesis is believed to be driven by bacterial invasion, replication, and spread within colonic intestinal epithelial cells (IECs).…”
Section: Introductionmentioning
confidence: 99%
“…resistance genes are often of plasmid origins, such as plasmid-mediated quinolone resistance (PMQR) genes namely qnr, or extended spectrum beta-lactamase (ESBLs)(Ranjbar & Farahani 2019). Other than that, phage profiling by PHASTER(Arndt et al 2016) showed 17 prophage regions, including 10 intact regions (Figure 1a).…”
mentioning
confidence: 99%
“…51 The genus Shigella contains bacteria closely related to E. coli and is comprised of four major pathogenic species: S. dysenteriae, S. flexneri, S. boydii, and S. sonnei. 21 Shigella can be transmitted from person-to-person, or through contaminated food sources and water ( Figure 1a), while some AMR Shigella outbreaks are associated with international travel and sexual transmission. 57 Shigella infections were once highly responsive to cheaper antibiotics such as β-lactams and antifolates, but rising resistance rates have shifted the treatments of choice toward macrolides or fluoroquinolones, with ceftriaxone as an alternative treatment option.…”
Section: Shigella Speciesmentioning
confidence: 99%
“…50 MDR Shigella can arise through plasmid-borne or integron-mobilized elements encoding multiple types of resistance. 21,54 A commonly observed MDR phenotype includes resistance to ampicillin, chloramphenicol, streptomycin, sulfonamides, and tetracyclines (ACSSuT). 21,24,58 Epidemics driven by MDR Shigella have risen worldwide within the last decade and requires significant intervention efforts to prevent further disease.…”
Section: Shigella Speciesmentioning
confidence: 99%